الإعلام الأمني الجديد وتحديات العنف والإرهاب - عبد الحميد, معتز محي (Sciences de l'Homme et de la Société, 2017)
إن عدم التخصص وضعف الخلفية المعرفية للقائمين على التغطية الإعلامية الأمنية التي تتعامل مع ظاهرة العنف والإرهاب أثر سلبا في إيجاد الحلول المناسبة لها، وحولها إلى مجرد تغطية سطحية وأحيانا تحريضية واتهامية تنطوي على اتهامات واحكام مسبقة وربما مبيتة، وجعلها عاجزة عن فهم خطاب الجماعات المتطرفة الإعلامي ومنظوماتها ومرجعياتها الفكرية والتنظيمية.  وعلى ضؤء ذلك سوف نتناول التطورات الواسعة في مهمات وأداء الإعلام الأمني الجديد أثناء أزمات العنف والإرهاب. Abstract :   The lack of specialization and weak knowledge of the media coverage of the phenomenon of violence and terrorism has negatively affected in finding appropriate solutions to them, and turned them into superficial coverage and sometimes provocative and accusation involving accusations and prejudices and may be buried, and make them unable to understand the rhetoric of extremist media groups and systems And its intellectual and organizational references. At the same time, we will address the broad developments in the missions and performance of the new security media during the violent and terrorist crises.